Power illusion in coalitional bargaining: An experimental analysis - Nicola Maaser; Stefan Traub; Fabian Paetzel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
In real world bargaining the distribution of seats or voting weights often does not accurately reflect real power. Game-theory predictions are insensitive to nominal differences. We refer to the converse idea that nominal differences matter as power illusion. We experimentally study the Baron-Ferejohn model with variation in nominal power. We find strong evidence for the existence of power illusion. Thus, attention needs to be paid to nominal power in the design of weighted voting systems.
Keywords: D72; C92; C7; 330